School Leadership in Developing Islamic Culture in Basic Schools 14 Kisam Tinggi District, Ogan Komering Ulu Selatan in 2020 - Nafisah, Binti Nur; Arafat, Yasir; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
The research objective was to identify and describe the principal's leadership in developing Islamic culture at SDN 14 Kisam Tinggi, Ogan Komering Ulu Selatan Regency in 2020. Researchers used a qualitative approach because the problems raised were social phenomena that required an understanding. Collecting data using observation, interviews and documentation. From the results of the research that has been done, it can be concluded that the leadership of the Madrasah Principal at SDN 14 Kisam Tinggi is capable. Furthermore, preserving the culture of studying books as a basis for moral development in students, then memorizing the Koran, carrying out tasmi 'al-quran every day on the classroom terrace before entering learning in class and a culture of shame from littering. The most frequent inhibiting factor comes from students who are naughty, and can't follow the existing rules. In developing an Islamic school culture it is necessary to have competent people in their fields